Big Data Analysis: Enables Internet of Things - Jayshree, Jadhav M; Chandraprabha, Kulkarni V (International Journal of Computer Sciences and Engineering, 2018)
The Big Data and Internet of Things (IoT) are two most emerging techniques in latest years. Data is created constantly & ever increasing rate. Different areas like mobile phones, social media, various medical imaging technologies & more creation of new data. This must be stored somewhere for some purpose. Big data is data whose scale, distribution, diversity, timeliness require the use of new technical architectures & analytics to enable insights that unlock new sources of business value. Internet Of Things is new revolution in abilities of the end point that are connected to the Internet. IoT is about devices, data and connectivity. The real value of Internet of Things is about creating smarter products, delivering intelligent insights and providing new business outcomes .This paper shows factors and relation between Big Data and Internet of Things. Huge data generated by different IoT devices must be analyzed by different Big Data Analytic tools.